A Review on Candida Auris, an Emerging Drug-resistant Fungal Pathogen - Fatemeh Safari; Kazem Ahmadikia; Hossein Mirhendi (مجله دانشکده پزشکی اصفهان, 2022)
Candida auris, a multidrug-resistant yeast, can cause primary or secondary infections in a wide range of patients, including those diagnosed with the new coronavirus to even healthy individuals. The fungus has been reported in less than a decade on all six continents and in more than 45 countries. Ease of distribution, long shelf life, and resistance to several antifungal drugs have raised concerns about the prevention and management of patients with C. auris infection. Recent reports indicate serious challenges in identifying, understanding the mechanism of drug resistance, and preventing mortality from the infection with this microorganism. Given the prevalence of COVID-19 infection, it is important to identify patients colonized with C. auris correctly and at the early stages, to control and prevent a possible outbreak. In this article, the widespread occurrence of infections due to C. auris in the world and Iran, its clinical manifestations, risk factors, pathogenic mechanisms, diagnostic enhancements and challenges, drug resistance, treatment options, prevention, and control as well as concomitant C. auris infections in patients with COVID-19 virus, are reviewed.